2021
DOI: 10.1007/s13205-021-02992-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria as biochemical energy source for the synthesis of inorganic nanoparticles, mechanism and potential applications: a review

Abstract: Green synthesis of nanoparticles (NPs) has gained great concern among researchers due to their unique properties, excellent applications and efficient route of synthesis. From the last decades, the number biologicals such as plants, fungus, bacteria, yeast, algae, and cyanobacteria and their products are using by various researchers for the synthesis of different NPs. However, the pillar of green chemistry keeps touching new heights to improve the performance. This review paper unveils almost recent cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 94 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Inorganic reducing agents are used in nanoparticle syntheses, such as silver and copper nitrate. Numerous inorganic nanoparticles have been employed in numerous scientific articles [13][14][15]. Among these, silver and copper nanoparticles are two that will be discussed in the subsections that follow.…”
Section: Glance Of Nanotechnologymentioning
confidence: 99%
“…Inorganic reducing agents are used in nanoparticle syntheses, such as silver and copper nitrate. Numerous inorganic nanoparticles have been employed in numerous scientific articles [13][14][15]. Among these, silver and copper nanoparticles are two that will be discussed in the subsections that follow.…”
Section: Glance Of Nanotechnologymentioning
confidence: 99%
“…The proposed method includes pathways of NADH dependent reductases along with shuttle quinone extracellular procedures. It was reported that depending upon the quantity of NADH formed, the synthesis of alloy of Au-Ag NPs with a variety of compounds was possible (Mubarakali et al, 2012;Bhardwaj and Naraian, 2021). The size of NPs formed has been observed to be dependent on synthesis conditions like fungal species used, temperature, pH, dispersion medium, etc.…”
Section: Fungimentioning
confidence: 99%
“…The above methods also utilized a very high temperature and pressure which is very harmful to the environment. Accordingly, the product cast is very high due to the higher order of the equipment used in these methods [7]. As a result, an environmentally friendly method is required to synthesize the NPs without utilizing any toxic components.…”
Section: Introductionmentioning
confidence: 99%